From Willard Straight to Wall Street : A Memoir - Jones, Thomas W. (Thomas Wade), 1949- (Book collections on Project MUSE., 2019)
"This is a memoir by Thomas W. Jones, the story of an African American who engaged in one of the most searing and traumatic campus confrontations of the 1960s in 1969 at Cornell University, and then transitioned to being one of the first wave of African Americans attempting to climb the ladder to the top ranks of corporate America. This story will help America to better understand both how far our country has progressed in race relations, and also how far we have yet to go. This story will help the black community to reflect on the dynamics of social and economic divisions within the black community. This story will help Americans of all colors and creeds and ethnicities to have hope for the future of our melting pot democracy"--